The Environmental Accounting Evolution: A Literature Review and Future Directions - Lilly Anggrayni; Alif Ilham Akbar Fatriansyah; Sofyan Tubagus (Kunuz: Journal of Islamic Banking and Finance, 2022)
The aim of this article is to track the trending topics in the field study of environmental accounting research. The data was analyzed by using the library study method. The data was collected from scopus database by searching the systematic keyword that related with the environmental accounting literature on the search engine. This study found that the article that discussed about the environmental accounting was various and mostly concern on the issue about carbon accounting, water accounting, and biodiversity accounting as well as the measurement stages of extinction accounting. The author also found there was some theory which fit with the environmental accounting research that mainly discussed about the evolution of modern accounting and business methods that now more concerned with the social and environmental accounting. This research had implication for the accounting thinkers as well as the accounting and economic students, because the author did not only discuss about the literature review of environmental accounting but also the future direction of the environmental accounting that could become a new novelty for the future study.